Exploring Joubert Syndrome: A Rare Case Study from Indonesia - Siswanto, Johanes Edy; Tasmina; Prayudijanto, Muhammad I.; Daniswara, Boromeus A.; Pamungkas, Christophorus A. S.; Pratanu, Lydia (Medicinus, 2025)
Background: Joubert Syndrome is a rare autosomal recessive disorder characterized by midbrain-hindbrain malformation and multisystem involvement. This study aims to present a detailed case of Joubert Syndrome from Indonesia, emphasizing clinical presentation, diagnostic challenges, and management strategies in a resource-limited setting. Methods: This descriptive case study examines a newborn female referred for breathing difficulties and a skull tumor present since birth. Data were collected through clinical evaluations, imaging studies, laboratory tests, genetic analysis, and multidisciplinary consultations. A literature review was conducted to compare the findings with global data. Result: The first case involved a female infant with hydrocephalus, a posterior skull mass, and microcornea. Echocardiography showed a patent foramen ovale, while genetic analysis confirmed a normal 46,XX karyotype. The second case featured a male infant with posterior meningocele, seizures, and retinal dystrophy. EEG confirmed subclinical seizures, and genetic testing identified pathogenic TMEM237 mutations consistent with Joubert Syndrome type 14. Both infants received respiratory support, antibiotics, and targeted treatments, resulting in significant clinical improvement. Conclusions: These cases highlight the importance of multidisciplinary care and genetic testing in Joubert Syndrome diagnosis and management. Early recognition, advanced diagnostics, and consistent follow-up are crucial for optimizing outcomes, particularly in resource-limited settings.